Cost-effectiveness of pulse oximetry and integrated management of childhood illness for diagnosing severe pneumonia - Solomon H. Tesfaye; Eskindir Loha; Kjell Arne Johansson; Bernt Lindtjørn (Public Library of Science (PLoS), 2022)
Pneumonia is a major killer of children younger than five years old. In resource constrained health facilities, the capacity to diagnose severe pneumonia is low. Therefore, it is important to identify technologies that improve the diagnosis of severe pneumonia at the lowest incremental cost. The objective of this study was to conduct a health economic evaluation of standard integrated management of childhood illnesses (IMCI) guideline alone and combined use of standard IMCI guideline and pulse oximetry in diagnosing childhood pneumonia. This is a cluster-randomized controlled trial conducted in health centres in southern Ethiopia. Two methods of diagnosing pneumonia in children younger than five years old at 24 health centres are analysed. In the intervention arm, combined use of the pulse oximetry and standard IMCI guideline was used. In the control arm, the standard IMCI guideline alone was used. The primary outcome was cases of diagnosed severe pneumonia. Provider and patient costs were collected. A probabilistic decision tree was used in analysis of primary trial data to get incremental cost per case of diagnosed severe pneumonia. The proportion of children diagnosed with severe pneumonia was 148/928 (16.0%) in the intervention arm and 34/876 (4.0%) in the control arm. The average cost per diagnosed severe pneumonia case was USD 25.74 for combined use of pulse oximetry and standard IMCI guideline and USD 17.98 for standard IMCI guideline alone. The incremental cost of combined use of IMCI and pulse oximetry was USD 29 per extra diagnosed severe pneumonia case compared to standard IMCI guideline alone. Adding pulse oximetry to the diagnostic toolkit in the standard IMCI guideline could detect and treat one more child with severe pneumonia for an additional investment of USD 29. Better diagnostic tools for lower respiratory infections are important in resource-constrained settings, especially now during the COVID-19 pandemic.